الهوية الايديولوجية في شعر محمد مهدي الجواهري - برزنجي, أ.د.إسماعيل إبراهيم مصطفى; محمد, م.م.مهدي حسين (Sulaimani Journal for Humanities, 2023)
This study aims to reach the ideological identity of Al-Jawahiri and clarify the changes that occurred in his thought, and shed light on these ideas that Al-Jawahiri adopted from the first incarnation or from his early childhood, by digging, taking the spatial and temporal environment in which he was born, and from which he inherited the ideas and Islamic and sectarian inclinations, and then moving to the capital, Baghdad, and acquaintance and mixing with his second home, which had the greatest impact on adoption and inclination to leftist thought, which was a major intellectual turning point in his life. The follower of Al-Jawahiri's poetry finds that his poetry was a mirror of the ideological changes in the Iraqi identity. Rather, it is invalid if we say that Al-Jawahiri in his personality and in his poetry represents the fluctuating and unstable Iraqi identity in its fullest form, and we find that the (I) of the poet identifies with (we) that represents his national affiliation and this identification It was necessary to preserve the identity of Iraq, which was and still is threatened by the coups and wars that were and still threaten its existence. The research concluded that Al-Jawahiri was a sectarian Islamist and a defender of his thought and doctrine, but he rejected what was not compatible with his progressive vision, and that the poet changed his ideology to leftism when he found that this ideology corresponded to a large extent with his vision.
Keywords: الهوية الايديولوجيا الأسلامية الجواهري اليسارية